Persepsi Masyarakat terhadap Tugas dan Fungsi Kepala Lingkungan Studi Kasus Lingkungan Bandar Khalipah, Kecamatan Percut Sei Tuan - Suteja, Juliadi; Zulkarnaen, Zulkarnaen (Lembaga Yasin AlSys, 2024)
The problem in this research is that many people in the Bandar Khalipah sub-district still do not know the duties and functions of the neighborhood head in their area, as well as the process for selecting the neighborhood head which is decided and chosen directly by the village head. This research uses qualitative research methods and sociological research whose object is the community in the Bandar Khalipah neighborhood, Percut Sei Tuan District. The results of the research show that the head of Ward VII Bandar Khalipah has a high level of concern for the people in his neighborhood. This can be seen from the performance of the Head of Ward VII Bandar Khalipah, who always prioritizes and prioritizes the needs of the community in various problems, providing easy public administration services to the community, so that the duties and functions of the Head of the Ward are carried out in accordance with applicable regulations. Apart from that, the head of Ward VII Bandar Khalipah is also always active and participates in religious activities held in his neighborhood. Apart from that, as head of the environment, of course he has several work programs that have been and will be realized, including: 1) posyandu activities which are routinely carried out once a month 2) social assistance programs (BLT) which are given to lower economic communities in the environment 3) mutual cooperation activities for cleaning environment which is routinely carried out once a month with the aim of creating a clean environment and strengthening harmony in the community 4) block paving installation program in the alleys in the VII Bandar Khalipah neighborhood. Thus, it can be concluded that in carrying out his duties and functions as head of Bandar Khalipah Environment VII he has been implemented well and in accordance with applicable regulations. However, in carrying out their duties and functions there are certainly obstacles that can hinder the realization of the planned work program.